A reflection on the practical implementation of the clinical governance framework in the Cape Winelands District of the Western Cape. Issue 6 (18th November 2016) - Gunst, Colette; Mash, Robert J; Phillips, Lizette Cathleen
Abstract : Primary health care is seen as the 'linchpin of effective health care delivery' by the Western Cape Government Health services and improving the quality of primary care, through clinical governance, is a key aspect of realising this vision. This article aims to provide an outline of the provincial clinical governance framework and to reflect on the experience and lessons learnt within the semi-rural Cape Winelands District in implementing this framework. Strategies that were used included the establishment of district clinical governance meetings; leadership development of both managers and family physicians, defining clinical governance activities and using routine monitoring and evaluation meetings as part of quality improvement cycles; developing clinicians competent to address the burden of disease; and focusing on establishing a primary health care approach in the district. Lessons learnt included that activities should take place within a supportive organisational culture with a focus on continuous quality improvement at all levels of the health system. A systematic approach to planning clinical governance at the district level should be balanced with a localised approach to encourage reflection, engagement and change. Recommendations for further implementation of clinical governance in the district are listed.